2013
DOI: 10.1371/journal.pone.0080944
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Toxic Potential of Graphene Copper Nanocomposite (GCNC) in the Third Instar Larvae of Transgenic Drosophila melanogaster (hsp70-lacZ)Bg9

Abstract: Graphene, a two-dimensional carbon sheet with single-atom thickness, have attracted the scientific world for its potential applications in various field including the biomedical areas. In the present study the graphene copper nanocomposite (GCNC) was synthesized, characterized and evaluated for its toxic potential on third instar larvae of transgenic Drosophila melanogaster (hsp70-lacZ)Bg9. The synthesized GCNC was analyzed by X-ray diffraction (XRD), scanning/transmission electron microscopy (SEM/TEM), atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…The flies were cultured on standard Drosophila food containing agar, corn meal, sugar and yeast at 25 °C (24 ± 1) [30]. Crosses were set up as described in our earlier published work [27]. The PD flies were allowed to feed separately on different doses of capsaicin (Sigma, USA) mixed in the diet.…”
Section: Drosophila Culture and Crossesmentioning
confidence: 99%
“…The flies were cultured on standard Drosophila food containing agar, corn meal, sugar and yeast at 25 °C (24 ± 1) [30]. Crosses were set up as described in our earlier published work [27]. The PD flies were allowed to feed separately on different doses of capsaicin (Sigma, USA) mixed in the diet.…”
Section: Drosophila Culture and Crossesmentioning
confidence: 99%
“…These results may be due to DNA repair occurred which differ from the study of Yousef et al (2010) that there were a higher DNA damage in the mature adults with respect to the long period of feeding of Shistocerca gregaria on clover treated with CdCl 2 and PbCl 2 reflects the absence of repair mechanism. But there are many studies used the comet assay to observe DNA repair in irradiated cells (Isabel and Maria, 2014) and in different cells of Drosophila after exposure to different genotoxic agents (Bilbao et al, 2002;Mukhopadhyay et al, 2004;Siddique et al, 2005bSiddique et al, , 2013García -Sar et al, 2012;Sharma et al, 2012;Mishra et al, 2014;Gaivã o et al, 2014;Isabel and Maria, 2014).…”
Section: Genotoxicity and Dna Repairmentioning
confidence: 99%
“…[4,191] For example, bimetallic conjugation of non-toxic parent materials Au and Pt with variable compositions has generated antimicrobial responses against E. coli, Salmonella choleraesius, and Pseudomonas aeruginosa by cell membrane damage and incremental increses in the intracellular level of adenosine triphosphate (ATP). [192] Recent studies involving grapheneZnO [193] and graphene-Cu [194] NHs showed increased toxicity in comparison to their parental components towards a model organism transgenic Drosophila melanogaster as demonstrated by enhanced lipid peroxidation and apoptosis. On the contrary, the presence of a silica-based shell structure reduced ZnO toxicity towards E. coli.…”
Section: Toxicitymentioning
confidence: 99%